Risk behaviors among Italian healthcare students: a cross-sectional study for health promotion of future healthcare workers - Belingheri, Michael; Facchetti, Rita; Scordo, Francesco; Butturini, Francesco; Turato, Massimo; De Vito, Giovanni; Cesana, Giancarlo; Riva, Michele Augusto (La Medicina del Lavoro, 2019)
Background: Risk behaviors are frequent among young adults and they are particularly relevant when considering healthcare students. Objectives: The study is aimed to examine the prevalence of smoking, binge drinking, physical inactivity, and excessive bodyweight in a population of healthcare students attending an Italian university. Methods: Healthcare students filled an anonymous multiple-choice questionnaire on the occasion of the occupational health visit that preceded their hospital internship. The questionnaire covered socio-demographic characteristics (including student’s working status and cohabitation) and risk behaviors. We evaluated the prevalence of risk behaviors and their association with socio-demographic characteristics. Results: The sample consisted of 494 students (65% women): 23.2% were smokers, 7.9% had excessive bodyweight, 35% did not practice any physical activity and 50% reported binge drinking at least once in the last 12 months. We found associations of male sex (30.5%) and being nursing students (29.9%) with smoking habit. The frequency of binge drinking was higher in men (38.4%), working students (53.9%), and among those who lived without family (50%). Physical inactivity was associated with female sex (44.2%) and living without family (57.1%). Finally, the co-presence of 2 risk behaviors or more was higher in men (36.8%), in nursing students (39.6%) and in working students (44.7%). Conclusions: Our findings regarding the prevalence of risk behaviors and their potential association with socio-demographic factors may be a clue to the definition of targeted strategies aimed at reducing of risk behaviors among healthcare students.